Effects of brown rice powder addition on nutritional composition and acceptability of two selected Malaysian traditional rice-based local kuih - Alice, C.L.V.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The present study was conducted to investigate the effects of brown rice (BR) powder addition on the proximate composition, total dietary fibre content and acceptability of some selected Malaysian traditional rice-based local kuih. Two types of kuih samples, namely Kuih Lompang (KL) and Kuih Talam Pandan (KTP) were prepared at the levels of either 0%, 10%, 20% or 30%. The kuih samples were analyzed for nutritional composition and sensory acceptance. There was significant increase in total dietary fibre content (from 2.64 g/100 g to 3.15 g/100 g) and protein content (from 2.36% to 2.51%) with the incorporation of 90% BR powder in the KL formulation. The moisture (from 36.79% to 36.83%), ash (from 1.11% to 1.21%) and fat (from 8.51% to 8.73%) content were not significantly affected for all percentages of BR powder addition. For KTP, the addition of BR powder at the level of 90% significantly increased the total dietary fibre (from 2.77 g/100 g to 3.45 g/100 g), fat (from 5.73% to 6.95%) and moisture (from 64.10% to 64.12%) content as compared to the control (0%). However, the protein content was not significantly affected (from 3.41% to 3.59%). On the other hand, there was no significant difference for all sensory attributes of KL formulated with 30-90% of BR powder as compared to the control (0%). The sensory score of KTP added with 30-90% BR powder received significantly lower sensory score compared to the control sample (0%) for appearance, colour, firmness, adhesiveness, chewiness, taste and overall acceptance attributes. In summary, sensory evaluation showed that all BR-incorporated KL were acceptable, while only 30% addition of BR powder in KTP was acceptable. Thus, BR powder is potentially used in improving the nutritional composition of KL. However, further study is needed to improve palatability aspect of KTP formulated with BR powder.